A framework for image synchronization from mobile NoSQL database to server-side SQL database - Zulkafli, A.Z. (Springer Verlag, 2017)
Last decades, software systems use SQL database to handle structured data between server and clients that hold text and integer value in column-store format. Nowadays, emergence of media entertainment had introduced unstructured data like images that acquires big memory allocation to be stored in database. Hence, some of software and mobile application developers tend to implement schema-less databases, which known as NoSQL. They handle synchronization process for unstructured data in a simple and fast manner. However, dissimilar database structure and framework make software developers tend to implement only either one type of databases: SQL or NoSQL, but not both. No interaction between SQL and NoSQL databases will prevent data sharing and accessibility. Hence, one-way image synchronization framework for heterogeneous databases in mobile environment has been developed and new sync gateway is introduced to synchronize images from client NoSQL database to server SQL database regardless of different schema and database structure. © Springer International Publishing AG 2017.